Considerations for the treatment of the supra condylea fracture of the humerus associated with nerve paralysis: study of a personal statistic of 145 cases - Bado, José Luis; Pedemonte, Pedro V; Lorenzo, Jorge (Cirugía del Uruguay, 2020)
Presented at session 30th May 1948